Expert System System Deteksi Gingivitis Gigi Menggunakan Certainty Factor - Eva Rianti; Firna Yenila; Hari Marfalino (Jurnal Teknologi, 2021)
Gingivitis is a disease in the form of abnormalities in the gingiva that can cause bleeding accompanied by swelling, redness, exudate, changes in normal contours which are sometimes considered normal by some patients even though it is considered serious by the Health Department. This study aims to educate the public in understanding the importance of knowing the condition of the body, especially the teeth that are most vulnerable to experience by the community. The lack of time required for consultation with experts resulted in this disease being left unattended. So it is necessary to develop IT-based consulting in the form of an expert system. The system is built using the certainty factor method. Certainty factor works by reading all the data submitted by the expert and gives the result in the form of the percentage of confidence the patient has gingivitis. Experts used in this system are dentists / dental specialists. The data were obtained from direct experts and the results of the consultations obtained new knowledge in the form of the percentage of the patient's confidence level with gingivitis. Data collection was obtained from Acute Gingivitis, Sub-Acute Gingivitis, Recurrent Gingivitis and Chronic Gingivitis as well as symptoms and solutions obtained from experts. This study contributes to a new service for patients who experience dental disease (gingivitis) without having to come directly to an appointed specialist. The level of accuracy of this system is quite helpful because the data source comes from direct experts so that the solution obtained can be an initial reference for patients before further treatment is carried out. The results of the study were in the form of softcopy and hardcopy that could be used as needed, based on the test data given to the patient, a 95% confidence level was obtained for the system trial results based on the patient's condition at that time. So that the results of the consultation are obtained in the form of information about the disease and the desired solution.